2022
DOI: 10.1161/circulationaha.122.059486
|View full text |Cite|
|
Sign up to set email alerts
|

Latent Pulmonary Vascular Disease May Alter the Response to Therapeutic Atrial Shunt Device in Heart Failure

Abstract: Background: In the REDUCE LAP-HF II trial, implantation of an atrial shunt device did not provide, overall, clinical benefit for patients with heart failure and preserved or mildly reduced ejection fraction (HFpEF/HFmrEF). However, pre-specified analyses identified differences in response in subgroups defined by pulmonary artery systolic pressure during submaximal exercise, right atrial (RA) volume, and sex. Shunt implantation reduces left atrial (LA) pressures but increases pulmonary blood flow, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 31 publications
2
79
1
1
Order By: Relevance
“…The recent REDUCE LAP-HF II trial failed to show a reduction in HF events after placement of an atrial shunt device in a population of HF patients with LVEF ⩾40% [689], with worse outcomes in the presence of PVD [690]. In addition, a sustained increase in PA blood flow may be a matter of concern, as this may trigger vascular remodelling in patients with pre-existing PH.…”
Section: Interatrial Shunt Devicesmentioning
confidence: 99%
“…The recent REDUCE LAP-HF II trial failed to show a reduction in HF events after placement of an atrial shunt device in a population of HF patients with LVEF ⩾40% [689], with worse outcomes in the presence of PVD [690]. In addition, a sustained increase in PA blood flow may be a matter of concern, as this may trigger vascular remodelling in patients with pre-existing PH.…”
Section: Interatrial Shunt Devicesmentioning
confidence: 99%
“…The authors argue that they can be explained simply by the fact that the decongestion of the left atrium led to more blood filling the right chambers. But when one looks at the aSD group at 12 months, left atrial size and E/e’ ratio had not changed 4 , suggesting that the left atrial function may have not improved. The authors also argue that this increase in volumes was not associated with a decrease in right ventricular function (judged via the echo surrogate marker of tricuspid annular plane systolic excursion); but it may be too early before a potential recent-onset PH may start affecting the right ventricular function.…”
Section: Potential Concern With the Long-term Use Of Asds In Humansmentioning
confidence: 99%
“…Thankfully, the authors had the insight to include, as a prespecified factor, exercise-induced increase in systolic pulmonary artery pressure at the baseline catheterization, which revealed a possible association of exercise-induced (but not resting) pulmonary pressures with the trial outcomes. In this issue of Circulation , Borlaug et al 4 present a post hoc analysis of the trial data. They show that patients with latent PH (defined by the authors as exercise-induced increase in pulmonary vascular resistance of ≥1.74 Wood Units, n=188) not only did not show benefit, but worsened clinically, including increased risk for heart failure events and decrease in the KCCQ score.…”
Section: Prespecified Post Hoc Analysis Of the Trial And Exercise-ind...mentioning
confidence: 99%
“…However, further post hoc analyses demonstrated that patients with peak exercise pulmonary vascular resistance < 1.74 WU appeared to benefit from the device (Fig. 6 ; [ 83 ]). Thus, future precision medicine trials of atrial shunt devices and procedures in HFpEF may benefit from only including those patients with the ability to vasodilate the pulmonary vasculature during exertion.…”
Section: Examples From Hfpef Clinical Trials That Have Informed Futur...mentioning
confidence: 99%